2014
DOI: 10.1186/1472-6882-14-141
|View full text |Cite
|
Sign up to set email alerts
|

Terminalia catappa attenuates urokinase-type plasminogen activator expression through Erk pathways in Hepatocellular carcinoma

Abstract: BackgroundThe survival rate of malignant tumors, and especially hepatocellular carcinoma (HCC), has not improved primarily because of uncontrolled metastasis. In our previous studies, we have reported that Terminalia catappa leaf extract (TCE) exerts antimetastasis effects on HCC cells. However, the molecular mechanisms of urokinase-type plasminogen activator (u-PA) in HCC metastasis have not been thoroughly investigated, and remain poorly understood.MethodsThe activities and protein levels of u-PA were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Huh7 cells treated with TCE led to a reduction in the activities, protein levels, and mRNA levels of u‐PA. TCE inhibited the effects of u‐PA by reducing the phosphorylation of ERK1/2 pathway . The present study revealed that TCE elicited antimetastatic effects on cervical cancer cells by inhibiting the activity of the MMP‐9 and ERK 1/2 pathways.…”
Section: Discussionsupporting
confidence: 56%
“…Huh7 cells treated with TCE led to a reduction in the activities, protein levels, and mRNA levels of u‐PA. TCE inhibited the effects of u‐PA by reducing the phosphorylation of ERK1/2 pathway . The present study revealed that TCE elicited antimetastatic effects on cervical cancer cells by inhibiting the activity of the MMP‐9 and ERK 1/2 pathways.…”
Section: Discussionsupporting
confidence: 56%
“…Terminalia catappa Linn. plant has been investigated in various pharmaceutical studies as it contains a variety of chemical components (Pandya et al, 2013; Yeh et al, 2014). T. catappa L. leaf extracts exhibit biological activities, including antioxidant (punicalagin, punicalin, terfluvina A and B, chebulic acid, benzoic acid, cumaric, and its derivatives) (Chen and Li, 2006; Chyau et al, 2006; Kinoshita et al, 2007), antidiabetic (β-carotene) (Anand et al, 2015), anticancer (punicalagin) (Naitik et al, 2012), antiviral (ellagic acid) (Tan et al, 1991), anti-inflammatory (triterpenic acids, especially ursolicacid and its derivatives) (Fan et al, 2004), antimicrobial (flavones and flavanols) (Kloucek et al, 2005; Nair and Chanda, 2008; Shinde et al, 2009), and hepato-protective activities (punicalagin, punicalin) (Kinoshita et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…(3) Alpha-l-fucosidase (AFU) is a lysosomal enzyme present in all mammalian cells and it has been proposed as a promising tumor marker since many studies reported increased AFU serum levels in patients with cirrhosis and HCC [96] . (4) Urokinase-type plasminogen activator(UROK) expression may be a potent therapeutic target of HCC [97] . (5) Peroxiredoxin 6 (PRDX6) may be a candidate biomarker for early HCC diagnosis [28] .…”
Section: Comparison Of Urinary Proteins In Different Tumor Modelsmentioning
confidence: 99%